The Mutational Landscape of Diffuse Large B Cell Lymphoma - Lohr, Jens; Stojanov, Petar; Lawrence, Michael S; Auclair, Daniel; Chapuy, Bjoern; Carter, Scott; Sougnez, Carrie; Gould, Joshua; Cruz-Gordillo, Peter; Cerhan, James R; Dogan, Ahmet; Habermann, Thomas M.; et al. (Blood, 2011)
Abstract 259 Despite recent progress, our understanding of the genomic basis of diffuse large B cell lymphoma (DLBCL) is incomplete. We have performed massively parallel whole exome sequencing with deep coverage of 57 primary tumor samples from patients with DLBCL and compared them to matched normal tissue to gain insight into the genetic defects leading to DLBCL. We define genes that are significantly enriched for somatic mutations, and thus, may be drivers of the disease. In addition to identifying genes that are well established to be functionally relevant in DLBCL, such as MyD88, CARD11, EZH2, and BCL2, we also discovered new genes that are significantly mutated that have not been described to play a role in DLBCL previously, such as MLL2, 3 and4 genes and PCLO. One of the challenges for the understanding of DLBCL biology is to determine the relative contribution of different genes with somatic mutations to the pathogenesis of the disease in an individual patient. Identification of functionally relevant mutated genes that only occur in a small number of patients based on prevalence alone may require thousands of patient samples. We therefore devise several strategies to discover genes with a high likelihood of functionally relevant mutations independent of their prevalence. Genes that do not co-occur with other mutated genes in the same patients, i.e. are mutually exclusive, are more likely to represent strong drivers, and to occur early in the development of DLBCL. We determined that TP53, BCL2, PIM1, and CD79B fall into this group. We apply pathway-focused analysis to identify mutated genes with low prevalence that are highly likely to have a functional impact. For instance, we identified G13D mutations in KRAS in two patients, and mutations in BRAF, NOTCH1, SOCS1, and PTEN in other patients that were previously described in other malignancies. These mutated genes are identified as part of significantly enriched gene sets, including the B cell receptor signaling/NFkB pathway, JAK/STAT, and antigen processing gene sets. In addition to these pathways that are important for physiological B cell activation, we find that many histone methyltransferases are enriched as a geneset in addition to MLL2. We identified a number of hotspots that are subject to somatic mutation. Our data imply that many of these hotspots may be targets of activation-induced cytidine deaminase (AID), which is usually involved in somatic hypermutation, suggesting a possible mechanism of how somatic mutation in DLBCL is mediated. In summary, our data define novel genetic defects in DLBCL by whole exome sequencing of 57 patients. Our data suggest that driver mutations may not be randomly distributed across the genome, but may occur in a directed fashion. We identified new genes not previously implicated in DLBCL, and have developed strategies to prioritize mutations that are most likely to be drivers of the disease. No relevant conflicts of interest to declare.